Does the Kuleshov Effect Really Exist? Revisiting a Classic Film Experiment on Facial Expressions and Emotional Contexts. (August 2016) - Barratt, Daniel; Rédei, Anna Cabak; Innes-Ker, Åse; van de Weijer, Joost
According to film mythology, the Soviet filmmaker Lev Kuleshov conducted an experiment in which he combined a close-up of an actor's neutral face with three different emotional contexts: happiness, sadness, and hunger. The viewers of the three film sequences reportedly perceived the actor's face as expressing an emotion congruent with the given context. It is not clear, however, whether or not the so-called "Kuleshov effect" really exists. The original film footage is lost and recent attempts at replication have produced either conflicting or unreliable results. The current paper describes an attempt to replicate Kuleshov's original experiment using an improved experimental design. In a behavioral and eye tracking study, 36 participants were each presented with 24 film sequences of neutral faces across six emotional conditions. For each film sequence, the participants were asked to evaluate the emotion of the target person in terms of valence, arousal, and category. The participants' eye movements were recorded throughout. The results suggest that some sort of Kuleshov effect does in fact exist. For each emotional condition, the participants tended to choose the appropriate category more frequently than the alternative options, while the answers to the valence and arousal questions also went in the expected directions. The eye tracking data showed how the participants attended to different regions of the target person's face (in light of the intermediate context), but did not reveal the expected differences between the emotional conditions.